STRATEGIES FOR THE PROMOTION OF SCHOOL ENTREPRENEURSHIP: A CASE STUDY - Corredor, Luis Alfonso Moreno; Santos, Luis Carlos Nova; Torres, Ligia Inés Melo (Journal of Posthumanism, 2024)
This study designs an action plan to effectively foster entrepreneurship at the Integrado Joaquín González Camargo Educational Institution. Addressing the need to consolidate an innovative culture, a diagnostic assessment was conducted to characterize the current curriculum, identify key variables for success, and evaluate the impact of the training received. The methodology uses a mixed-methods approach, with a descriptive analysis based on structured surveys of 71 students in the business management track. The findings reveal a program with a solid foundation but significant challenges: a moderate perception of the quality of knowledge acquired, a weak connection between theory and practical application, and a critical need to strengthen intrinsic motivation, soft skills, and linkages with the business and academic ecosystem. In response, this work proposes comprehensive strategies oriented toward pedagogical innovation, such as project-based learning; the creation of an entrepreneurship lab as a permanent space for prototyping and co-creation; and the strengthening of strategic partnerships with universities and the business sector for mentorship programs. The ultimate goal is to transform the school environment into an incubator for autonomous and creative young people, capable of conceiving entrepreneurship as a powerful driver of personal and social development.